Two new benthic Euphilomedes Kornicker, 1967 (Ostracoda, Myodocopida, Philomedidae) from the Taiwan Strait (East China Sea) - Peng Xiang; Xiaoyin Chen; Ruixiang Chen; Jinghong Lin; Yu Wang; Youyin Ye; Mao Lin (PeerJ, 2017)
Ostracods are small bivalved crustaceans widely distributed in aquatic environments and in total 99 species have been recorded in genus Euphilomedes Kornicker, 1967. In this study, we further describe two new species of benthic ostracods in this genus, Euphilomedes liuruiyii sp. nov. and Euphilomedes pentacanthos sp. nov., collected from the Taiwan Strait in China. These two species can be easily distinguished from their congeners by some crucial morphological characteristics, including the carapace shape, the numbers of main and secondary furcal claws, and their arrangement of furcal claws. In addition the first antenna, endopod of second antenna, frontal organ, mandible and the seventh limb also differentiate these two species from related species.